ETHICAL PRINCIPLES IN HOSPITAL SETTINGS – PERCEPTIONS OF INTERN DOCTORS OF TERTIARY CARE HOSPITAL (Journal of Forensic Medicine & Toxicology, 2021)
Background: Ethics in hospital setting is very much essential for intern doctors to learn and acquire certain principles of ethics to practice in community in future. Present study was aimed to investigate the perceptions of intern doctors towards ethical principles in hospital setting. Materials and methods: All intern doctors of GMERS Medical College, Gujarat were subjected to pre-tested and pre-validated Likert’s scale type questionnaire (1 to 5, 1 – Strongly Disagree, 5 – Strongly agree) regarding ethical principles in hospital setting. Study was done after obtaining ethical approval from the Institutional Ethical Committee. Data obtained were analyzed via median score and tabulated.
Keywords: Ethical Principles; Hospital Setting; Intern Students; Perceptions